IDIOSINKRASI KATA BELAJAR DAN PELAJAR DALAM BAHASA INDONESIA - Hendrik Jehane (Jurnal Lazuardi, 2020)
Most Indonesian wards are formated through derivation process. The Derivation process has an impact on changing categories, forms, and meanings. Each dervative word generaly has a linear meaning relationship with the basic word. Word shape changes generaly have certain pattern that are regular so that produce consistent rules of word formation. There are two problems in this reseach, (1) how is the relation between the meaning of the word belajar dan pelajar with the basic word ajar?; (2) how is the morphological process of forming the word belajar and pelajar?. The purpose of this study was to examine the relationship between the meaning of the word belajar and pelajar with the basic word ajar, and the morphological process of forming word belajar and pelajar. The method used is deskriptive method because the object of this study is the language that is alive and used by the speakers. The result of the research that (1) the relation of word meaning belajar and pelajar is not linear with the basic word but is opositive, (2) the process of changing phonem /r/ to /l/ in words belajar and pelajar the reason cannot be explained morphophonemically; resulting in idiosyncrasy. To avoid idiosyncrasy, it is better to belajar word and pelajar recorded as an entry in Indonesian standard dictionary.